Personal Pronoun Errors in Seventh Grade Descriptive Texts: A Purworejo Case Study - Purnomo, Edi; Rokhayati, Titi; Tusino, Tusino (Scripta : English Department Journal, 2024)
This study examines personal pronoun errors in descriptive texts written by seventh-grade students in Purworejo, Indonesia. A sample of 16 students, comprising 8 males and 8 females, was analyzed to identify common error patterns. Errors were categorized into four types: omission, addition, misformation, and misordering. Results showed that omission errors were the most frequent, constituting 43% of the total, followed by misformation errors at 37%, addition errors at 14%, and misordering errors at 7%. The study highlights specific challenges these learners face in using personal pronouns correctly in English. Understanding these error patterns is essential for educators aiming to develop targeted teaching strategies. Findings suggest that focused interventions on personal pronouns can significantly improve students' writing skills. Future research should explore effective teaching methods to address these errors and enhance ESL learners' proficiency in English writing. This study contributes to the limited research on personal pronoun errors among Indonesian ESL students and emphasizes the need for tailored educational approaches.